THE EFFECT OF SOCRATIC CIRCLES METHOD WITH IMAGES MEDIA CRITICAL ON THINKING SKILLS OF STUDENTS GRADE XI MIA SMA 1 SUNGGAL STATE IN MATERIAL HUMAN REPOSISTORY SYSTEM - Steffanie Mutiara Meha; Adriana Yulinda D. LumbanGaol; Elfi Julianida Daulae (Jurnal Pelita Pendidikan, 2017)
This research was aimed to find out the influence of Socratic Circles method with imagemedia and critical thinking skills and Interaction between lerning method and critical thinking skills????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????skills of students in class XI MIA SMA Negeri 1 Sunggal on thematerial of human respiration system. This research is a quasi experimental research and conductedin class XI MIA SMA Negeri 1 Sunggal, using factorial design 2 x 2 and a sample of 72 students whotake it based on random sampling. Inferential statistic test used two-way ANAVA. Test datarequirement is normality test with Kolmogorov-Smirnov test and homogeneity test of variance with???????????????????????????????? . According X ± SE variance analysis result (ANAVA) show thats: (1) The result of criticalthinking skills of students taught by Socratic Circles method with image media 80±1.26 higher thanthe result of critical thinking skills taught by discussion method 65±1.59 in SMA Negeri 1 Sunggal;(2) The result of students with high critical thinking skills 78.78±1.22 higher than the result ofstudents with low critical thinking skills 65.86±1.90; and (3) There is interaction between lerningmethod and critical thinking skills to the students critical thinking skills. The interaction betweenlerning method and critical thinking skills have a significant effect on students critical thinking skills(Fhitung=3.320; P=0.073).Key words: Socratic Circles method, image media, critical thinking skills